Relativistic Particle Beams as a Resource to Solve Outstanding Problems in Space Physics - Sanchez, Ennio R.; Powis, Andrew T.; Kaganovich, Igor D.; Marshall, Robert; Porazik, Peter; Johnson, Jay; Greklek-Mckeon, Michael; Amin, Kailas S.; Shaw, David; Nicolls, Michael (Frontiers in Astronomy and Space Sciences, 2019)
The Sun’s connection with the Earth’s magnetic field and atmosphere is carried out through the exchange of electromagnetic and mass flux and is regulated by a complex interconnection of processes. During space weather events, solar flares or fast streams of solar atmosphere strongly disturb the Earth’s environment. Often the electric currents that connect the different parts of the Sun-Earth system become unstable and explosively release the stored electromagnetic energy in one of the more dramatic expressions of space weather – the auroral storm and substorm. Some aspects of the magnetosphere-ionosphere connection that generates auroral arcs during space weather events are well-known. However, several fundamental problems remain unsolved because of the lack of unambiguous identification of the magnetic field connection between the magnetosphere and the ionosphere. The correct mapping between different regions of the magnetosphere and their foot-points in the ionosphere, coupled with appropriate distributed measurements of plasma and fields in focused regions of the magnetosphere, is necessary to establish unambiguously that a given magnetospheric process is the generator of an observed arc. The three most important problems for which the correct magnetic field mapping would provide closure to are the substorm growth phase arcs, the expansion phase onset arcs and the system of arcs that emerge from the magnetosphere-ionosphere connection during the development of the early substorm expansion phase phenomenon known as substorm current wedge (SCW). Energetic electron beams, used as magnetic field tracers, can enable the closure needed. However, the application of beams as tracers require demonstration that the beams can be injected into the loss cone, that the spacecraft potentials induced by the beam emission are manageable, and that sufficient electron flux reaches the atmosphere to be detectable by optical or radio means after the beam has propagated thousands of kilometers under competing effects of beam spread and constriction as well as effects of beam-induced instabilities. In this communication we provide a review of the latest results of synergistic research carried out under the NSF INSPIRE program to address these challenges and discuss the next steps toward the realization of active experiments in space using relativistic electron beams.